Hydroponics and elicitation, a combined approach to enhance the production of designer secondary medicinal metabolites in Silybum marianum - Mubeen, Bismillah; Hasnain, Ammarah; Mehboob, Riffat; Rasool, Rabia; Riaz, Ayesha; Elaskary, Shymaa Abdelsattar; Shah, Muhammad Muntazir; Faridi, Tallat Anwar; Ullah, Inam (Frontiers in Plant Science, 2022)
Medicinal plants have been used to cure human diseases since decades. Silybum marianum, a medicinal plant, is regarded as a source of secondary metabolites with therapeutic value against liver diseases and diabetes. The present study was conducted to enrich the production of secondary metabolites in the vegetative parts of Silybum marianum using elicitation strategy in hydroponic system with different elicitors. The elicitors of fungus Aspergillus niger (0.2 g/L), methyl jasmonate (MeJA) (100 μM) and silver nanoparticles (AgNPs) (1 ppm) were added in hydroponic medium, individually and in combination form to the 15 days old plant. The elicitor-treated plants were harvested at different time points (24–144 h; increment 24 h) and their biochemical parameters like phenolics, flavonoids, nitric oxide (NO), and superoxide dismutase (SOD) were analyzed. The results showed hyper-accumulation of these biochemical contents, especially in response to MeJA (100 μM), followed by AgNPs (1 ppm) and co-treatment of AgNPs (1 ppm) with other elicitors. The results revealed that the treatment with MeJA (100 μM) exhibited the highest flavonoid (304 μg g–1), phenolic (372 μg g–1), and SOD (16.2 U g–1) contents. For NO levels, the maximum value of 198.6 nmole g–1 was achieved in response to the treatment with MeJA + Green synthesized AgNPs (100 μM + 1 ppm). Our findings depicted an enhanced production of medicinally important plant secondary metabolites and antioxidants; hence, the method applied in this study can play a significant role to improve therapeutic values of the plants.